2004
DOI: 10.1242/jcs.00845
|View full text |Cite
|
Sign up to set email alerts
|

FAK promotes organization of fibronectin matrix and fibrillar adhesions

Abstract: Targeted disruption of the focal adhesion kinase (FAK) gene in mice is lethal at embryonic day 8.5 (E8.5). Vascular defects in FAK-/- mice result from the inability of FAK-deficient endothelial cells to organize themselves into vascular network. We found that, although fibronectin (FN) levels were similar, its organization was less fibrillar in both FAK-/- endothelial cells and mesoderm of E8.5 FAK-/- embryos, as well as in mouse embryonic fibroblasts isolated from mutant embryos. FAK catalytic activity, proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 41 publications
(39 reference statements)
5
95
0
Order By: Relevance
“…FAK is a critical regulator of FN matrix assembly as FAK-null cells do not assemble an FN matrix (59). We found that phosphorylation on FAK Tyr-397 was significantly higher in cells on a rigid substrate after 2 h compared with those on a soft substrate.…”
Section: Gј Ementioning
confidence: 73%
“…FAK is a critical regulator of FN matrix assembly as FAK-null cells do not assemble an FN matrix (59). We found that phosphorylation on FAK Tyr-397 was significantly higher in cells on a rigid substrate after 2 h compared with those on a soft substrate.…”
Section: Gј Ementioning
confidence: 73%
“…The compact conformation of FN dimers is maintained by intramolecular interactions involving the type III 12-14 repeats of FN. 53,54 The type III [12][13][14] repeats, also known as heparin II binding domain, interact with the HS chains from various members of the Sdc family. 55 Binding of Sdc1 with heparin II may facilitate unfolding of dimeric FNs and expose FN self-assembly (FN-binding) sites, thus promoting FN deposition and fibrillogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant engagement of Sdc4 and integrins promotes Rho GTPase and focal adhesion kinase (FAK) activities, which are crucial for efficient initiation of FN matrix assembly. [12][13][14][15] Sdc1 is expressed primarily by epithelial and plasma cells of healthy adult tissue. 16 Recently, we and others 17,18 observed the induction of Sdc1 in stromal fibroblasts of invasive breast carcinomas.…”
mentioning
confidence: 99%
“…Interestingly, fakÀ/À fibroblasts similarly exhibit a defect in fibronectin matrix assembly (Ilic et al, 2004). This defect can be rescued by re-expression of wild-type FAK, but not by FAK397F, nor by a FAK mutant that is impaired for binding p130 CAS (Ilic et al, 2004). Together these findings suggest that the FAK/SFK complex may be the active signaling component promoting assembly of the fibronectin matrix and that p130 CAS may be an important downstream effector for this function.…”
Section: Role Of Src Kinases In the Assembly Of Fibronectin Matrixmentioning
confidence: 92%
“…Second, pharmacological inhibition of Src family kinases also impairs the assembly of a fibronectin matrix (Wierzbicka-Patynowski and Schwarzbauer, 2002). Interestingly, fakÀ/À fibroblasts similarly exhibit a defect in fibronectin matrix assembly (Ilic et al, 2004). This defect can be rescued by re-expression of wild-type FAK, but not by FAK397F, nor by a FAK mutant that is impaired for binding p130 CAS (Ilic et al, 2004).…”
Section: Role Of Src Kinases In the Assembly Of Fibronectin Matrixmentioning
confidence: 99%